Kolaborasi antara Guru Bahasa Arab, Orang Tua dan Terapis dalam Mendukung Pembelajaran Bahasa Arab Anak Berkebutuhan Khusus di Sekolah Inklusi - Hasan, Laili Mas Ulliyah; Nurharini, Firdausi; Hasan , Izzah Nur Hudzriyah (Global Action and Education for Society, 2024)
This research explores the role of collaboration between teachers, parents and therapists in supporting Arabic language learning for children with special needs in an inclusive school environment. Through a qualitative approach, data was collected through in-depth interviews with Arabic teachers, students' parents, and therapists involved in the learning process. The findings show that effective collaboration between the three parties is the key to success in facilitating Arabic language learning for children with special needs. Factors such as open communication, understanding students' individual needs, curriculum adjustments, and emotional and social support have proven important in creating an inclusive learning environment that supports the growth and language development of children with special needs. The practical and pedagogical implications of this research highlight the importance of interdisciplinary collaboration and support the role of each stakeholder in strengthening Arabic language learning in inclusive schools. This research contributes to further understanding of collaborative strategies that can be implemented in inclusive education contexts to support children with special needs in achieving progress in their Arabic language.